Cross-Cultural Studies (Institutional Knowledge at Singapore Management University, 2001)
On the occasion of his 90th birthday, Mr Choor Singh, a retired judge of the Supreme Court of Singapore, made a donation to launch Singapore Management University's Centre for Cross-Cultural Studies (now known as the Wee Kim Wee Centre). The centre is to be a platform for research, discussion and teaching across political, geographical and cultural boundaries. Left to right: Deputy President Tan Teck Meng, Mrs Choor Singh, Mr Choor Singh and President Janice Bellace. Photo taken on 18 January 2001. Mr Choor Singh passed away in 2009, aged 98.